Analisis Tingkat Kepuasan Kinerja Operasional Bus Trans Banjarmasin Dengan Menggunakan Metode Importance Performance Analysis - Hendra Putra; Hendri Yani Saputra (Pusat Penelitian dan Pengabdian Kepada Kepada Masyarakat Politeknik Negeri Tanah Laut, 2025)
Banjarmasin City has a feeder-based public transportation mode, namely the Trans Banjarmasin Bus, which began to operate actively in February 2020 to reduce the increase in private vehicles, which caused a rise in traffic volume. With several operational as many as 3 (three) corridor routes that have been operational within 3 (three) years, it is necessary to assess operating performance and how the expectations of the community, especially passengers with facilities and services on the Trans Banjarmasin Bus, to know the extent of the value of conformity between performance and operational expectations by the community with the Trans Banjarmasin Bus service. Based on these problems, assessment steps are carried out related to the performance and functional expectations of the Trans Banjarmasin Bus based on perceptions or opinions by the community where the results of the assessment are analyzed using the level of a suitability assessment and the Importance Performance Analysis method which obtains results in the form of quadrant diagrams. Using a questionnaire containing as many as 60 question variables obtained based on SPM regulations and previous research studies, the questionnaire was distributed to 120 respondents, especially Trans Banjarmasin Bus passengers. The results of collecting operational performance assessment data and operational expectations carried out by analysis with conformity level assessment obtained the average value of Trans Banjarmasin Bus performance, and functional expectations of 98.4903, and with analysis using the Importance Performance Analysis method obtained as many as 14 variables in the position of Quadrant A, as many as 34 variables in the part of quadrant B, as many as 1 (one) variables that are in the amount of quadrant C, and 11 variables that are in the position of quadrant D. In conducting continuous research. It is expected to find solutions and efforts in making operational improvements to the performance of the Trans Banjarmasin Bus to community expectations.